PRODUKSI DAN APLIKASI VAKSIN DNA Streptococcus iniae UNTUK MENINGKATKAN IMUNITAS NILA (Oreochromis niloticus) - Sutanti Sutanti; Novi Megawati; Sugiyo H. Pranoto; Ratu Siti Aliah (Universitas Gadjah Mada, 2016)
DNA vaccine Streptococcus iniae is a third generation of vaccines based on the gene encoding a vaccine antigen. Pgm is DNA-binding protein that activates expression of several important virulence gene, including those encoding polysaccharide capsule. The pgm gene controlled by MBA promoter has constructed successfully as a candidate of DNA vaccine to against S. iniae infection in Nile Tilapia. The goals of this study were to production and application of DNA Vaccine S. iniae to increase the nile tilapia immunity. Vaccine production was using plasmid isolation method from Escherichia coli dH5α containing pMBA-pgm. Vaccine verification was was accomplished by PCR using pgm gene S. iniae Fstrep and Rstrep specific primers, which revealed the 1,713 bp PCR product. Application of DNA vaccine was using 25, 50, 75, and 100ng/ml dosage with intraperitonial injection method .The challenge test was using 108 cfu/ml density of S. iniae. Observation test parameter were survival rate, relative percent survival, mean time to death, pgm gene, and organ histology such as liver, eyes, brain, spleen and kidney. Vaccine production was succeed using plasmid isolation method and containing pgm gene revealed 1713bp. the application of DNA vaccine was optimum at 50ng/ml dosage with SR value 96.667%, RPS value 88,461% and MTD value 4,6 days. The eyes histology shows opacity and exopthalmia, the other organ such as liver, spleen and kidney was necrosis. The DNA vaccine was optimum at 50ng/ml dosage.